Mitral valve replacement with the preservation of the entire valve apparatus Substituição da valva mitral com preservação do aparato completo da valva - Ahmed A. Alsaddique (Brazilian Journal of Cardiovascular Surgery, 2007)
OBJECTIVE: The papillary muscles and the chordae tendineae of both mitral leaflets contribute to the preservation of the left ventricular function. Most surgeons, however, routinely excise the anterior mitral leaflet. METHODS: In a group of nine patients, six of them underwent mitral valve replacement alone and three underwent both aortic and mitral valve replacements, all the mitral apparatus was preserved. All of these patients had mechanical valves using CarboMedics cardiac prosthesis (CarboMedics, Inc. Austin, Texas). RESULTS: There was no mortality. Postoperative echocardiographic assessment revealed maintained left ventricular function with no interference with the prosthetic leaflet mobility and no left ventricular outflow tract gradient. CONCLUSION: We believe that in most patients with long-standing mitral valve regurgitation, thinned out papillary muscles and elongated chordae tendineae that are not amenable to repair, valve replacement with the preservation of the entire native valve is possible and should be encouraged. This is especially valuable for those with depressed left ventricular function, who might otherwise suffer from left ventricular dysfunction in the long-term if the entire mitral valve apparatus were to be excised. OBJETIVO: Os músculos papilares e as cordas tendíneas de ambos folhetos mitral contribuem para a preservação da função ventricular esquerda. Muitos cirurgiões, entretanto, rotineiramente extirpar o folheto mitral anterior. MÉTODOS: Em um grupo de nove pacientes, seis deles foram submetidos à substituição da válvula mitral e três foram submetidos a substituições das válvulas mitral e aórtica, todos os aparatos mitrais foram preservados. Todos os pacientes tinham válvulas mecânicas implantadas usando próteses cardíacas CarboMedics (CarboMedics, Inc. Austin, Texas). RESULTADOS: Não houve mortalidade. A avaliação ecocardiográfica pós-operatória revelou a conservação da função ventricular esquerda sem interferencia da mobilidade protética do folheto e não tinha gradiente da via de saída do ventrículo esquerdo. CONCLUSÃO: Acreditamos que, na maioria dos pacientes com regurgitação da válvula mitral crônica, uma redução no número dos músculos papilares e com as cordas tendíneas alongados que não favorecem os reparos, a substituição da válvula com a preservação inteira da válvula nativa é possível e deve ser encorajada. Isso é especialmente benéfico para aqueles pacientes com a função ventricular esquerda deprimida que podem, ao contrário sofrer de disfunção ventricular ao longo prazo se o aparato da válvula mitral fosse ser extirpada.